Gender Interpretation in Husein Muhammad’s Tafsir: Women’s ‎Leadership and Religious Scholarship from the Perspective of Mubadalah - Hafidh Dinul Kholis; Wafik Azizah; Ahmad Yusam Thobroni; Muhammad Ainudzaky (Universitas Islam Negeri Imam Bonjol Padang, 2025)
Issue leadership and clerics Woman in Islam still become debate in various circles. Many interpretations of gender in Islam tend to be patriarchal and restrictive roles of women in the room public. However, the approach Recitation Mubādalah offers more perspective-inclusive and gender-equitable. Research This aims to examine the interpretation of gender on social media, in particular through Husein Muhammad's Facebook status, which consistently discusses the role Woman as leaders and scholars. With the use method of qualitative descriptive and approach Recitation Mubādalah, research analyzes how to interpret gender as more egalitarian and can applied to understanding of contemporary Islam. Research results show that Husein Muhammad put forward an interpretation that emphasized mutual gender relations. In his view, women own equal rights and capacities with men in leadership and religious studies. Analysis of his Facebook status shows that social media become a means effective in spreading thinking progressive related to gender interpretation. In conclusion, the approach of Recitation Mubādalah opens room for more interpretation fair for Women in Islam. Research This confirms that social media can play a role in reconstructing a better understanding of religion.